Civil society - Edwards, Michael, 1957-. (Cambridge; Polity Press, 2014)
'Recent global unrest has shown the importance of social movements and street protests in world politics. However, the power that people have to shape their societies is usually channeled through day-to-day participation in voluntary associations and communities: expressions of'normal' civic life beyond the headlines. This is the underlying story of civil society. This new edition of a standard work of reference explores issues that have developed rapidly in recent years, including the overlaps between civil society and the market in the form of social enterprises and'venture philanthropy,' and the increasing role of social media and information and communication technologies in civic interaction. Different varieties of civil society in the Middle East, Africa and elsewhere are investigated in more detail, and case studies, data and references have been updated throughout. Colleges, foundations and NGOs, policy-makers, journalists and commissions of inquiry--all have used Edwards's book to understand and strengthen the vital role that civil society can play in deepening democracy, re-building community, and addressing inequality and injustice. This new edition will be required reading for anyone who is interested in creating a better world through voluntary citizen action.'--Page 4 of cover.
Introduction : what's the big idea? -- Civil society as associational life -- Civil society as the good society -- Civil society as the public sphere -- Synthesis : unraveling the civil society puzzle -- So what's to be done?
Includes bibliographical references (pages 143-166) and index.
Keywords: Civil society; Social contract